KEMAMPUAN INTELLIGENCE QUOTIENT (IQ) MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS SAM RATULANGI - Mangiwa, Rinto; Wungouw, H. I. S.; Pangemanan, D. H. C. (Universitas Sam Ratulangi, 2014)
Abstract: In education, intelligence utilized to determine the extent of achievement of learning that can be achieved by an individual. Intelligence factors that result in the difference between someone with another intelligence is innate, environmental, physical condition, social background and socioeconomic. Research purposes to describe the ability of qoutient intelligence ( IQ ). Descriptive survey study was conducted using the method of cross -sectional study to measure the ability of student’s Intelligence Quotient ( IQ ) of the Faculty of Medicine, University of Sam Ratulangi. Number of respondents 100 people, consisting of 50 men and 50 women. Based on the results obtained IQ `measurement capability results in 11 respondents ( 22 % ) of male respondents have the ability IQ with Superior category, the other 11 people ( 22 % ) categorized as Above Average, the remaining 28 men ( 56 % ) had Average IQ ability . Women on the ability of IQ respondents only 1 ( 2 % ) are categorized as Superior, 9 people ( 18 % ) categorized as Above Average, and the remaining 40 ( 80 % ) were classified as having the ability IQ category average. Keywords: Intelligence Capabilities Qoutien, Student’s. Abstrak: Dalam bidang pendidikan, intelegensi dimanfaatkan untuk mengetahui sejauh mana prestasi belajar yang dapat dicapai oleh suatu individu. Faktor-faktor intelegensi yang mengakibatkan terjadinya perbedaan antara intelegensi seseorang dengan yang lain yaitu pembawaan, lingkungan hidup, kondisi fisik, latar belakang sosial ekomoni dan pendidikan. Tujuan penelitian untuk mengetahui gambaran kemampuan intelligence qoutient (IQ). Penelitian dilakukan secara survey deskriptif dengan mengunakan metode cross sectional study untuk mengukur kemampuan Intelligence Quotient (IQ) mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi. Jumlah responden 100 orang, terdiri dari Laki-laki 50 orang dan Perempuan 50 orang. Berdasarkan hasil penelitian pengukuran kemampuan IQ diperoleh hasil pada responden 11 orang (22%) responden laki-laki memiliki kemampuan IQ dengan kategori Superior, sebanyak 11 orang (22%) masuk kategori diatas rata-rata, sisanya 28 orang (56%) memiliki kemampuan IQ rata-rata. Pada responden perempuan pada kemampuan IQ hanya 1 orang (2%) yang masuk kategori Superior, 9 orang (18%) masuk kategori diatas rata-rata, dan sisanya 40 orang (80%) memiliki kemampuan IQ yang tergolong kategori rata-rata. Kata kunci: Kemampuan Intelligence Qoutient, mahasiswa.